2018
DOI: 10.1016/j.virol.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of malacoherpesvirus proteins: Pan-herpesvirus capsid module and replication enzymes with an ancient connection to “Megavirales”

Abstract: The order Herpesvirales includes animal viruses with large double-strand DNA genomes replicating in the nucleus. The main capsid protein in the best-studied family Herpesviridae contains a domain with HK97-like fold related to bacteriophage head proteins, and several virion maturation factors are also homologous between phages and herpesviruses. The origin of herpesvirus DNA replication proteins is less well understood. While analyzing the genomes of herpesviruses in the family Malacohepresviridae, we identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 72 publications
4
28
0
Order By: Relevance
“…Although there were multiple recent attempts to build phylogenies of PolBs ( 3 , 24 , 28 ), our current work differs from the previous analyses in two major ways. First, our dataset was enriched by metagenomic sequences and contained nearly 3000 sequences (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although there were multiple recent attempts to build phylogenies of PolBs ( 3 , 24 , 28 ), our current work differs from the previous analyses in two major ways. First, our dataset was enriched by metagenomic sequences and contained nearly 3000 sequences (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 94%
“…PolBs are also encoded by many DNA viruses with larger genomes, mainly belonging to the order Caudovirales (head-tailed viruses of Archaea and Bacteria), Nucleo-Cytoplasmic Large DNA Viruses (NCLDV) and several other families of eukaryotic viruses such as baculoviruses and herpesviruses. In a recent study, Mushegian and colleagues showed that PolBs encoded by eukaryotic viruses form two clades, one including NCLDVs (excluding Poxviridae and Asfarviridae ), Hytrosaviridae and Herpesviridae and the other one containing Alloherpesviridae , Malacoherpesviridae , Poxviridae , Baculoviridae and Nimaviridae ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…The power of multi-parameter classifications described in the current study and elsewhere [ 32 ] is that outputs from improved structure modelling methods can be directly slotted into the processing pipeline and virus relationships re-evaluated within the same overall computational framework. Such methods may greatly expand the depth of phylogenetic trees constructed from CGJ distances and reveal considerably more about their deeper evolutionary relationships, perhaps including those currently apparent by morphology alone [ 36 , 43 , 44 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our search for OsHV-1-encoded miRNAs suggested that OsHV-1 does not utilize miRNAs. This was not self-evident since other viruses related to OsHV-1 [ 6 ], as well as WSSV [ 16 , 63 ] can encode miRNAs. However, the OsHV-1 sncRNA reads showed a size distribution lacking abundant size classes typical of miRNAs.…”
Section: Discussionmentioning
confidence: 99%